Microleakage comparison of four dental materials as intra-orifice barriers in endodontically treated teeth - Yavari, Hamid Reza; Samiei, Mohammad; Shahi, Shahriar; Aghazadeh, Mohammad; Jafari, Farnaz; Abdolrahimi, Majid; Asgary, Saeed (Iranian Endodontic Journal, 2011)
Introduction: The aim of this in vitro study was to compare polymicrobial microleakage of calcium enriched mixture (CEM) cement, mineral trioxide aggregate (MTA), amalgam, and composite resin as intra-orifice sealing materials. Materials and Methods: Seventy single-rooted mandibular premolars were instrumented and obturated by cold lateral compaction technique. The teeth were randomly divided into four experimental groups according to used material: CEM, MTA, amalgam and composite resin (n=15) and two control groups (n=5). In experimental groups, 2 mm of coronal gutta-percha was removed and replaced with the study material. All the teeth were mounted in a two-chamber apparatus and the coronal portion was exposed to human saliva. The day the turbidity occurred was recorded for each sample. Data were analyzed using one-way ANOVA. Results: The negative control group showed no leakage while the average microleakage time in the positive control group was 3.5 days. The average bacterial leakage times for amalgam, composite resin, MTA, and CEM groups were 27.42±3.6, 29.35±3.15, 52.57±2.87, and 50.42±2.73 days, respectively. There was no significant difference between CEM and MTA groups (P=0.27) and also between amalgam and composite resin groups (P=0.36). However, in term of average leakage time, MTA and CEM groups exhibited significant differences with amalgam and composite resin groups (P<0.001). Conclusion: According to the results of the present in vitro study, in terms of coronal sealing in endodontically treated teeth, CEM and MTA are more effective than amalgam and composite resin.